2018
DOI: 10.1371/journal.pone.0203513
|View full text |Cite
|
Sign up to set email alerts
|

GI-16 lineage (624/I or Q1), there and back again: The history of one of the major threats for poultry farming of our era

Abstract: The genetic variability of Infectious bronchitis virus (IBV) is one of the main challenges for its control, hindering not only the development of effective vaccination strategies but also its classification and, consequently, epidemiology understanding. The 624/I and Q1 genotypes, now recognized to be part of the GI-16 lineage, represent an excellent example of the practical consequences of IBV molecular epidemiology limited knowledge. In fact, being their common origin unrecognized for a long time, independen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…This is likely also the case of the GVI-1 lineage. Thus, we speculate that some of the so called "emerging" genotypes may actually be ancient genetic groups that have not been correctly identified or classified (Franzo et al, 2018). Based on the VN results, strains LHB/110615 and I0221/17 were found to be of the same serotype and shared 94.9% antigenic relatedness; however, despite the comparative sequence conservation of the S1 subunit for the GVI-1 viruses in this study, obvious antigenic diversity was also found.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This is likely also the case of the GVI-1 lineage. Thus, we speculate that some of the so called "emerging" genotypes may actually be ancient genetic groups that have not been correctly identified or classified (Franzo et al, 2018). Based on the VN results, strains LHB/110615 and I0221/17 were found to be of the same serotype and shared 94.9% antigenic relatedness; however, despite the comparative sequence conservation of the S1 subunit for the GVI-1 viruses in this study, obvious antigenic diversity was also found.…”
Section: Discussionmentioning
confidence: 60%
“…This hypothesis can be confirmed by the availability and analysis of the complete genomic sequences of the CO8089L/CO8091Llike strains in Colombia and GVI-1 viruses in Asian countries. Increasing evidence shows that the circulation of many "novel" genotypes and lineages often predate their first identification (Franzo et al, 2017(Franzo et al, , 2018. This is likely also the case of the GVI-1 lineage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comprehensive studies of Polish IBV isolates from 1998 to 1999 using serological and molecular tests conducted in cooperation with Italian researchers showed that the 793B type was a major component of the IBV population in Poland during this period, but serologically the presence of 624/I isolates was also identified and one isolate even showed no serological cross-reaction in an HI test nor amplification in RT-PCR (Capua et al, 1999). Recently, the 624/I and Q1 types were determined to affiliate to the GI-16 lineage, which has been present in Europe (Italy) since 1963 and persists until now (Franzo et al, 2018). In the period 2011-2013 numerous cases of D1466 IBV (GII-1 lineage) were detected, however, in subsequent years (2014)(2015), the number of D1466-positive samples dropped to 3.1%, and currently we do not detect these viruses at all (Domanska-Blicharz et al, 2012;Domanska-Blicharz et al, 2017).…”
Section: Discussionmentioning
confidence: 98%